Improving the anti-diabetic and anti-hyperlipidemic activities of extra virgin olive oil by the incorporation of diallyl sulfide: Bioactivities of diallyl sulfide-rich olive oil - Habibi, Emna; Baâti, Tarek; Selmi, Slimen; M’Rabet, Yassine; Njim, Leila; Ashraf, Syed Amir; Humaidi, Jamal R.; Hamadou, Walid Sabri; Snoussi, Mejdi; Emira, Noumi; Anouar, El Hassane; Hosni, Karim (Cellular and Molecular Biology, 2024)
Development of novel functional foods is trending as one of the hot topics in food science and food/beverage industries. In the present study, the anti-diabetic, anti-hyperlipidemic and histo-protective effects of the extra virgin olive oil (EVOO) enriched with the organosulfur diallyl sulfide (DAS) (DAS-rich EVOO) were evaluated in alloxan-induced diabetic mice. The ingestion of EVOO (500µL daily for two weeks) attenuated alloxan-induced elevated glucose, alanine transaminase (ALT), aspartate transaminase (AST), alkaline phosphatase, lactate dehydrogenase (LDH), urea and creatinine. It also normalized the levels of triglycerides (TG), total cholesterols (TC), low-density lipoprotein-cholesterol (LDL-c) and their consequent atherogenic index of plasma (AIP) in diabetic animals. Additionally, EVOO prevented lipid peroxidation (MDA) and reduced the level of hydrogen peroxide (H2O2) in diabetic animals. Concomitantly, it enhanced the activity of the antioxidant enzymes catalase (CAT), glutathione peroxidase (GPx) and superoxide dismutase (SOD), reducing thereby tissue oxidative stress injury. The overall histologic (pancreas, liver, and kidney) alterations were also improved after EVOO ingestion. The manifest anti-diabetic, lipid-lowering and histo-protective properties of EVOO were markedly potentiated with DAS-rich EVOO suggesting possible synergistic interactions between DAS and EVOO lipophilic bioactive ingredients. Overall, EVOO and DAS-rich EVOO show promise as functional foods and/or adjuvants for the treatment of diabetes and its complications.